1970
DOI: 10.1111/j.1460-2466.1970.tb00875.x
|View full text |Cite
|
Sign up to set email alerts
|

Group Credibility and Opinion Change

Abstract: The purpose of this study was to determine the effect of messages of varying ethos upon opinion change. The results support the hypothesis that messages attributed to a High Ethos Group are more influential than those attributed to a Collection of High Ethos individuals, a High Ethos individual, a Low Ethos Group, and a Collection of Low Ethos individuals.A number of investigators have demonstrated that written communications designed to persuade can have an impact on their readers [6, 71. Researchers have als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
2006
2006

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The credibility of the attorney's attempting to persuade prospective jurors is also an important factor in the success of such an attempt, since there is considerable support for the proposition that the greater the perceived credibility of the source, the greater the potential persuasive impact of that source (Aronson, Turner, & Carlsmith, 1963;Cohen, 1964;Hovland & Weiss, 1951;Johnson, Torcivia, & Poprick, 1968;Meyers & Goldberg, 1970;Sigall & Helmreich, 1969). Although a number of dimensions contribute to a source's credibility, the two that have been most frequently cited are the source's expertise and objectivity (Hovland, Janis, & Kelley, 1953).…”
Section: Methods Of Indoctrinationmentioning
confidence: 99%
“…The credibility of the attorney's attempting to persuade prospective jurors is also an important factor in the success of such an attempt, since there is considerable support for the proposition that the greater the perceived credibility of the source, the greater the potential persuasive impact of that source (Aronson, Turner, & Carlsmith, 1963;Cohen, 1964;Hovland & Weiss, 1951;Johnson, Torcivia, & Poprick, 1968;Meyers & Goldberg, 1970;Sigall & Helmreich, 1969). Although a number of dimensions contribute to a source's credibility, the two that have been most frequently cited are the source's expertise and objectivity (Hovland, Janis, & Kelley, 1953).…”
Section: Methods Of Indoctrinationmentioning
confidence: 99%
“…First, it suggested to her audience that her perspective was based on careful reflection of all the relevant issues coupled with little or no bias or animosity. Myers and Goldberg (1970) found that the perception of careful deliberation significantly influenced subjects' persuasibility. Secondly, autonomy elevated the senator's rhetorical status because it enhanced the perception of her objectivity.…”
Section: The Mutability Of Rhetorical Status In Changing Circumstancesmentioning
confidence: 97%